Financial Risk, Managerial Capability, and MSME Business Resilience in an Era of Economic Uncertainty - Irwan Moridu; Nurcahya Hartaty Posumah; Fitriani Fitriani (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines how perceived financial risk and managerial capability are associated with MSME business resilience under economic uncertainty. Business resilience is defined as the capacity to anticipate, absorb, adapt to, and recover from disruption. Methodology – A quantitative nationwide online survey was conducted in Indonesia. Google Forms questionnaires were distributed through a third-party respondent panel platform to eligible MSME owners and managers. The final sample comprised 200 valid responses and was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Finding/Results – Perceived financial risk was negatively associated with business resilience, whereas managerial capability was positively associated with it. Managerial capability showed the stronger standardized association within the specified model, which explained 86.2% of the variance in business resilience. These results are interpreted cautiously because the data are cross-sectional and self-reported. Originality/Value – Rather than claiming new direct relationships, this study offers an integrated dual-mechanism explanation of MSME resilience: financial vulnerability constrains the resources available for responding to disruption, while managerial capability supports the sensing, coordination, and reconfiguration of those resources. Its contribution is the joint assessment of these mechanisms and their relative statistical associations within one model.